National Research Strategies: what outcomes are important in peri‐operative elderly care?. (January 2014) - Peden, C. J.; Grocott, M. P. W.
Summary: Outcomes are essential measures of healthcare effectiveness and efficiency. Traditional measures of outcome, such as mortality and length of stay, are important and easy to measure but have significant limitations when evaluating the peri‐operative care of elderly patients. Alternative measures, including clinician‐described (e.g. complication rates, functional status, frailty) and patient‐reported outcome and experience measures, are important to provide a comprehensive description of peri‐operative outcome in the older patient. However, few measurement tools have been developed or validated specifically for the elderly surgical patient. This paper describes the outcome measures currently in use, explores how they might be used to improve the quality of care provision, and indicates priority areas for peri‐operative outcomes research in the elderly surgical patients.